Excitotoxicity: Still Hammering the Ischemic Brain in 2020 - Choi, Dennis W. (Frontiers in Neuroscience, 2020)
Interest in excitotoxicity expanded following its implication in the pathogenesis of ischemic brain injury in the 1980s, but waned subsequent to the failure of N-methyl-D-aspartate (NMDA) antagonists in high profile clinical stroke trials. Nonetheless there has been steady progress in elucidating underlying mechanism. This review will outline the historical path to current understandings of excitotoxicity in the ischemic brain, and suggest that this knowledge should be leveraged now to develop neuroprotective treatments for stroke.